Begonia xuansonensis, a new orange-flowered species of Begoniaceae from northern Vietnam - Do, Truong Van; Shui, Yu-Min; Le, Phuc Van; Huynh, Hue Thu Thi; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Nuraliev, Maxim S. (Phytotaxa, 2021)
Begonia xuansonensis, a new species from northern Vietnam, is described and illustrated. The new species is characterized by reddish-orange to orange tepals, which is a rare type of flower coloration in Asian species of the genus. Begonia xuansonensis is most similar to B. lowiana, but differs from the latter by stipules 4–6 × 1.5–2 mm, orange tepals and ovary, and abaxially densely red setose inner tepals of staminate and pistillate flowers. The new species also shows similarity with B. cathayana, differing in stipules 4–6 mm long, uniformly dark green adaxial side of leaf blade, abaxially densely red setose inner tepals of a staminate flower and three styles in a pistillate flower. Begonia xuansonensis is tentatively assigned to B. sect. Platycentrum on the basis of actinomorphic androecium, apically rounded anthers and fruit with three unequal wings. Morphological description and detailed photographs of the new species are provided, accompanied by information on its ecology, provisional conservation status, and a taxonomic comparison with similar species.